Role of Internal Halal Committee in Ensuring Business Sustainability: The Case of a Multinational Slaughter House (Journal of Business Management and Accounting, 2020)
For an industry, business sustainability is a critical aspect to be addressed by the company to remain relevant in an ever competitive market demand. In doing so, one of the strategies that can be taken is through adhering to all laws and legal requirements, particularly on halal aspect. The establishment of the Internal Halal Committee (IHC) is part of the requirement stipulated by the Malaysia Guidelines on Halal Assurance System 2011 (HAS 2011) and Manual Procedure for Malaysia Halal Certification (Third Revision) 2014 (MPPHM 2014). These laws must be read together with standards, Fatwa decisions, and regulations which are enforced pertaining to Malaysia Halal Certification. The law requires the establishment of IHC together with the appointment of a halal executive, supervisor, and also checkers in order to ensure that products are in accordance with standards prescribed by the law and Shariah principles in Malaysia. By adopting a case study approach involving a multinational slaughter house, this article highlights the practice taken up by Jimat Jaya Sdn. Bhd. The study employed interviews and non-participatory observation for data collection. It was revealed that strict legal requirements imposed by the government on halal products and compliance by the company have helped the company to gain more confidence from its existing and potential customers in relation to their products, hence ensuring sustainability of the business in the market.